2010
DOI: 10.1002/adsc.200900902
|View full text |Cite
|
Sign up to set email alerts
|

Morpholinium Trifluoroacetate‐Catalyzed Aldol Condensation of Acetone with both Aromatic and Aliphatic Aldehydes

Abstract: We report a highly efficient, general and practical method for the aldol condensation of acetone with aromatic and aliphatic aldehydes, using morpholinium trifluoroacetate as a catalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 37 publications
2
46
0
Order By: Relevance
“…[3b] As et of unsaturated methyl ketones was therefore prepared and tested as potential Michael acceptor substrates (Supporting Information, Scheme S1). [9] Thek etones were expected to react with Lys83, the catalytic amine,t of orm ac ovalently bound iminium intermediate,w hich could be attacked by appropriate nucleophiles.Michael additions of 1a-1g with arange of donor molecules (2a-2e)w ere performed in the presence of RA95.5-8 and monitored by HPLC (see the Supporting Information for details). Although most combinations afforded only small amounts of the new products,the reaction of 1aand ethyl 2-cyanoacetate (2a)was particularly rapid and high-yielding (Scheme 1b).…”
mentioning
confidence: 99%
“…[3b] As et of unsaturated methyl ketones was therefore prepared and tested as potential Michael acceptor substrates (Supporting Information, Scheme S1). [9] Thek etones were expected to react with Lys83, the catalytic amine,t of orm ac ovalently bound iminium intermediate,w hich could be attacked by appropriate nucleophiles.Michael additions of 1a-1g with arange of donor molecules (2a-2e)w ere performed in the presence of RA95.5-8 and monitored by HPLC (see the Supporting Information for details). Although most combinations afforded only small amounts of the new products,the reaction of 1aand ethyl 2-cyanoacetate (2a)was particularly rapid and high-yielding (Scheme 1b).…”
mentioning
confidence: 99%
“…To our delight, pyrrolidine ( 4c ) gave the desired 2‐pyridone ( 5 ) with 44% yield (entry 3). Aziridine ( 4a ) was found to be ineffective (entry 1), while treatment with azetidine ( 4b ), piperidine ( 4e ) , and morpholine ( 4f ) led to very low yields (entry 2, 5, and 6).…”
Section: Resultsmentioning
confidence: 99%
“…Also, reusability study revealed 0.4 ppm leaching of Pd with some metal agglomeration over the support. Zumbansen et al [17] have used morpholinium trifluroacetate as a catalyst which is most likely to be an ionic liquid. The catalyst gave 80% yield of raspberry ketone after 12 h of reaction time.…”
Section: Effect Of Temperature On Hydrogenation Of Phba To Raspberry mentioning
confidence: 99%
“…At optimum conditions, the yield of raspberry ketone obtained after 5 h was 82.5%. Morpholinium trifluoroacetate, an ionic liquid like compound, was examined for the aldol condensation of aliphatic aldehyde such as p ‐hydroxybenzaldehyde and acetone . An attempt was made by Climent et al.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation